Implementation of School Management Based on Educational Standard Process at SMPN 2 Kampar Kiri Hilir in Kampar - Jama’awati; Daviq Chairilsyah; Arza Aibonotika (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This article covers how to plan, organize, implement, and supervise school management in creating education at SMPN 2 Kampar Kiri Hilir District in Kampar. The research uses a qualitative approach with descriptive methods. Data collection techniques use documentation, observation, and interviews. The research subjects involve school principals, deputy principals, teachers, employees/staff, school supervisors, committees, and student representatives at SMPN 2 Kampar Kiri Hilir District in Kampar. The results of the research show that 1) the implementation of the school management planning function in implementing educational process standards at SMPN 2 Kampar Kiri Hilir in Kampar can be categorized as good, 2) the organization of school management in implementing standard educational processes at SMPN 2 Kampar Kiri Hilir in Kampar is good, 3) the implementation of school management in implementing educational process standards at SMPN 2 Kampar Kiri Hilir in Kampar is quite good, and 4) the supervision of school management in implementing standard educational processes at SMPN 2 Kampar Kiri Hilir in Kampar can be classified as good, as seen from the supervision carried out by the principal and school supervisor. Therefore, it can be concluded that the implementation of planning, organizing, implementing, and supervising school management in creating education at SMPN 2 Kampar Kiri Hilir in Kampar overall is applied well.